Curcumin, A Potential Therapeutic Candidate for Anterior Segment Eye Diseases: A Review - Liu, Xiu-Fen; Hao, Ji-Long; Xie, Tian; Mukhtar, Nour Jama; Zhang, Wiley; Malik, Tayyab Hamid; Lu, Cheng-Wei; Zhou, Dan-Dan (Frontiers in Pharmacology, 2017)
Curcumin, the major curcuminoid of the turmeric, has been extensively used in many countries since ancient time for preventing and/or treating a multitude of diseases. This review is to illustrate the researches on the properties of curcumin and its potential therapeutic efficacy in major anterior segment eye diseases. The bio-medical potential of curcumin is restricted because of its low solubility and digestive bioavailability. This review will discuss promising research in improving curcumin bioavailability through structural modification. In vitro and in vivo research made progress in studying the beneﬁcial effects of curcumin on major anterior segment eye diseases, including anti-angiogenesis effect in corneal diseases; anti-inflammation or anti-allergy effects in dry eye disease, conjunctivitis, anterior uveitis; anti-proliferation and pro-apoptosis effects in pterygium; anti-oxidative stress, anti-osmotic stress, anti-lipid peroxidation, pro-apoptosis, regulating calcium homeostasis, sequestrating free radicals, protein modification and degradation effects in cataracts; neuroprotective effects in glaucoma. Curcumin exhibited to be a potent therapeutic candidate for treating those anterior segment eye diseases.